Cellular and Molecular Inflammatory Profile of the Choroid Plexus in Depression and Suicide - Devorak, Julia; Torres-Platas, Susana Gabriela; Davoli, Maria Antonietta; Prud’homme, Josée; Turecki, Gustavo; Mechawar, Naguib (Frontiers in Psychiatry, 2015)
The inflammatory hypothesis of depression is one of the main theories that endeavors to explain and describe the underlying biological mechanisms of depression and suicide. While mounting evidence indicates altered peripheral and central inflammatory profiles in depressed patients and suicide completers, little is known about how peripheral and central inflammation might be linked in these contexts. The choroid plexus (ChP), a highly vascularized tissue that produces cerebrospinal fluid (CSF) and lacks a blood-brain-barrier, is an interface between peripheral and central immune responses. In the present study, we investigated the cellular and molecular inflammatory profile of the ChP of the lateral ventricle in depressed suicides and psychiatrically healthy controls. Gene expression of macrophages, pro- and anti-inflammatory cytokines, and various factors implicated in immune cell trafficking were measured; and density of ionized calcium binding adaptor molecule 1-positive (Iba1+) macrophages associated with the ChP epithelial cell layer (ECL) was examined. Significant downregulations of the genes encoding interleukin 1ß (IL1ß), a pro-inflammatory acute-phase protein; intercellular cell adhesion molecule 1 (ICAM1), a protein implicated in immune cell trafficking in the ChP; and IBA1, a monocyte/macrophage marker; were detected in depressed suicides as compared to controls. No difference in the density of Iba1+ macrophages associated with the ChP ECL was observed. While interpretation of these findings is challenging in the absence of corroborating data from the CSF, peripheral blood, or brain parenchyma of the present cohort, we hypothesize that these present findings reflect a ChP compensatory mechanism that attenuates the detrimental effects of chronically altered pro-inflammatory signaling caused by elevated levels of pro-inflammatory cytokines, such as IL-1ß, peripherally and/or centrally. Together, these findings further implicate neuroimmune processes in the etiology of depression and suicide.